Waterfall Method In The Development Of Information Systems In Supporting Transactional In Small Businesses - Basmar, Muh. Fahmi; Yusuf, Muh.; Rachmat, Rachmat (INFOKUM, 2022)
The application of the Waterfall technique to the development of sales information systems in small organizations is one way to increase sales process efficiency and effectiveness. The Waterfall technique is an organized and sequential approach to software development that begins with an analysis of user requirements and proceeds to system design. In this study, the Waterfall method is applied to the development of a sales information system determined by specifications for a small business with a relatively simple business process, namely the sales transaction process related to improving services in business transactions and the process of ordering items related to the inventory of items in the warehouse to be able to control whether items need to be restocked. The design employs a structured method, the Data Flow Diagram (DFD), beginning with the context diagram, DFD level, table design with the Conceptual Data Model (CDM), and interface design for the sales transaction process and arranging transactions.